Pengaruh Metode AIR dalam Penggunaan Kata Tanya terhadap Hasil Belajar Mata Pelajaran Bahasa Indonesia di SDN 008 Palembang - tasia; Ramanata Disurya; Etty Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aimd to improve students' learning outcomes in the Indonesian language subject, especially in the material on the use of interrogative words, by implementing the Auditory, Intellectual, and Repetition (AIR) learning method. Initial observations in class II of SDN 008 Palembang showed that most students had not achieved the Learning Objective Achievement Criteria (KKTP) set at 70, with only 19 out of 36 students meeting the standard. This low learning outcome was caused by conventional learning methods that did not actively involve students and the lack of variation in teaching techniques. The AIR method was implemented as an alternative solution that focused on the aspects of listening (Auditory), thinking (Intellectual), and repetition (Repetition). With this approach, students were encouraged to be more active, think critically, and strengthen their memory of the material being studied. The results of the study showed that the application of the AIR method could improve students' activeness, understanding, and learning outcomes in composing and using interrogative sentences correctly. Therefore, the AIR method is considered effective in learning Indonesian at the elementary school level. Keywords: AIR method, learning outcomes, data collection and presentation